EFL SPEAKING STUDENTS’ ATTITUDES TOWARDS TASK-BASED LANGUAGE TEACHING - Alhomaidan, Dr. Abdullah M. A. (IJRDO- Journal of Educational Research, 2017)
This study explores the value of task-based language teaching in English as a foreign language (EFL) speaking classes from the perspective of forty intermediate level students studying in a technical Saudi Arabian college, who had been extensively exposed to this type of teaching. Several research hypotheses were formulated on the basis of a comprehensive literature review of scholarship on speaking and task-based language teaching and then tested in this research context. The study uses quantitative data derived from anonymous, semi-structured questionnaires distributed to students. The results of this study show that the majority of respondents appear to hold an overwhelmingly positive attitude regarding the employment of task-based language teaching in their speaking courses.